The Study of The Influence of Vehicle Body Aerodynamics on Energy Consumption in Electric Vehicles Using Integrated CFD Simulation - Muhammad Alwi; Yultan Demmanggasa; Kartini Yunus; Andi Abustan Fahar; Irvan Darmawan A. Djamro (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study examines the impact of vehicle body aerodynamics on energy consumption in electric vehicles (EVs) using integrated Computational Fluid Dynamics (CFD) simulations. The problem addressed is the significant role of aerodynamic drag in reducing EV efficiency and range. The research aims to explore how aerodynamic optimizations, such as body shape adjustments, can reduce drag and improve energy efficiency. Primary data was collected from CFD simulations of various vehicle designs, and secondary data was gathered from relevant literature. The findings indicate that aerodynamic modifications, combined with other design optimizations like battery and motor efficiency improvements, lead to substantial reductions in energy consumption, demonstrating the importance of a holistic approach to vehicle design for enhanced EV performance and sustainability.